(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information about ways to improve the technical skills of wrestlers, about techniques and tactics, and about the mechanisms for training technical skills, technical training is the basis of the skill of the wrestler, stable sets of each training and training, available situations, the initial kick of the opponent.